Lexical-Semantic, Morphological And Linguocultural Distinctive Features Of The Arabic Language (The Journal of Interdisciplinary Human Studies, 2026)
Arabic is one of the oldest living languages, serving as the official language of more than twenty states and as the liturgical language of over 1.8 billion Muslims worldwide. This article provides a scientific analysis of the linguistic nature and unique structural features of Arabic, focusing specifically on its root-and-pattern morphological system, its inflective morphology, and its incomparable semantic richness. The article examines the phenomenon of diglossia in the Arabic language, the productivity of its synonym and antonym systems, the stylistic functions of majaz (figurative expression) within the discipline of balagha (rhetoric), and the linguocultural connections between Arabic and Uzbek. The study argues that Arabic constitutes a unique global linguistic phenomenon whose features are best understood through a combination of structural- linguistic and culturological analytical approaches.
Keywords: Arabic language; morphology; root-and-pattern system; semantics; diglossia; majaz; balagha; Arabisms; linguoculturology; Uzbek-Arabic contact; trilateral root